2013
DOI: 10.1016/j.jpsychores.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mental disorders and the common cold in adults: A population-based cross-sectional study

Abstract: Conclusion:The presence of a DSM-IV mental disorder was associated with a 44% higher risk of having experienced a cold in the past 12 months. Further studies are needed to explore potential common risk factors for incidence of mental disorders and the common cold, since the pathway connecting them has not been fully determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…26,[31][32][33] For example, the PSS-10 was used in an induced influenza A study, and was shown to predict symptom scores, mucus weight, IL-6 from nasal wash. 34 As a clinical syndrome, anxiety is prevalent, leading to substantial public health impact and is associated with several illness states, including the common cold. 35 To assess anxiety, the Spielberger State Trait Anxiety Scale 28 has been used in numerous studies. [36][37][38] The randomized trial of mindfulness meditation by Davidson et al found improvement in Spielberger anxiety scores at the end of 8 weeks of MBSR training and 4 mo afterwards (P < 0.01), as well as an increase in IgG response to influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…26,[31][32][33] For example, the PSS-10 was used in an induced influenza A study, and was shown to predict symptom scores, mucus weight, IL-6 from nasal wash. 34 As a clinical syndrome, anxiety is prevalent, leading to substantial public health impact and is associated with several illness states, including the common cold. 35 To assess anxiety, the Spielberger State Trait Anxiety Scale 28 has been used in numerous studies. [36][37][38] The randomized trial of mindfulness meditation by Davidson et al found improvement in Spielberger anxiety scores at the end of 8 weeks of MBSR training and 4 mo afterwards (P < 0.01), as well as an increase in IgG response to influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory infection (ARI), including common cold, influenza, and influenza-like-illness, is very common, and leads to substantive morbidity, mortality, and economic harms. Evidence suggests that psychological, social and behavioral factors influence susceptibility to ARI illness [1][2][3][4]. For example, people with higher levels of perceived stress [5][6][7][8], emotional reactivity [9], recent stressful life events [10,11], and negative emotional styles [12,13] are at greater risk for ARI illness.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these milder infections may affect the central nervous system through the same pathways as severe infections , that is, through inflammation and/or autoimmune responses , and some smaller studies have indicated that even mild infections may increase the risk of mental disorders . Furthermore, several studies have shown that infections and also the treatment with antibiotics can cause changes in the gut microbiome, which has been suggested to be implicated in the etiology of mental disorders .…”
Section: Introductionmentioning
confidence: 99%